Highly thermal conductive graphene/carbon nanotubes films with controllable thickness as thermal management materials. Issue 6 (15th March 2023) - Xiong, Ke; Ma, Cheng; Wang, Jitong; Ge, Xiang; Qiao, Wenming; Ling, Licheng
Abstract: As electronic devices continue to be integrated and miniaturized, the increased system power density leads to a continued increase in operating temperature, ultimately leading to degradation of stability and performance. Therefore, the development of thermal management materials with superior thermal conductivity is urgently needed. Herein, full-carbon graphitized graphene/carbon nanotubes (CNTs) (gGC) films with controlled thickness were fabricated through compositing followed by compaction. The appropriate amount of CNTs doping enlarges the crystallinity and improves the stacking order of the composite film during the structural evolution process. Ultimately, the thermal synergy between CNTs and graphene sheets accelerates the propagation of phonons and endows the free-standing gGC film with good performance. The flexible gGC film shows an in-plane thermal conductivity of 1280.3 W/mK, an electrical conductivity of 6559 S/cm, and the foldability of 10, 000 times at a thickness of 30 μm. Moreover, gGC films with controllable thicknesses were successfully prepared through a convenient "multilayer compaction" strategy, which allows thick gGC films to maintain a high level of thermal dissipation, while effectively mitigating the rapid decline in thermal conductivity of the films with increasing thickness. This work provides a general method for the realization of large-scale and convenient production of high-thermally conductive thick films.